2022
DOI: 10.1002/acn3.51640
|View full text |Cite
|
Sign up to set email alerts
|

Trigeminovascular effects of propranolol in men and women, role for sex steroids

Abstract: Objective Assess whether propranolol modulates the trigeminovascular system in both men and women. Methods We investigated the effect of propranolol (80 mg, 90 min after oral administration, corresponding to T max ) on the increase in dermal blood flow of the forehead skin (innervated by the trigeminal nerve) by capsaicin application (0.6 mg/mL) and electrical stimulation (0.2–1.0 mA) before and after placebo (grapefruit juice) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 46 publications
0
5
0
Order By: Relevance
“…Another limitation is the inclusion of patients who take migraine preventatives. In the case of beta‐blockers, DBF seems indeed to be influenced 38 . We performed a sensitivity analysis with these participants under beta‐blockers and did not see any different results.…”
Section: Discussionmentioning
confidence: 89%
See 1 more Smart Citation
“…Another limitation is the inclusion of patients who take migraine preventatives. In the case of beta‐blockers, DBF seems indeed to be influenced 38 . We performed a sensitivity analysis with these participants under beta‐blockers and did not see any different results.…”
Section: Discussionmentioning
confidence: 89%
“…In the case of beta-blockers, DBF seems indeed to be influenced. 38 We performed a sensitivity analysis with these participants under beta-blockers and did not see any different results. However, this should be considered in further studies.…”
Section: Discussionmentioning
confidence: 97%
“…Although the key mechanisms and sites of action for medications used in migraine prevention remain unclear, it seems that almost all affect the trigeminal CGRP system indirectly [ 116 , 117 ]. They inhibit CGRP release and consequently reverse sensitization in chronic migraine [ 116 , 118 ].…”
Section: Antimigraine Drugs That Modulate Cgrpmentioning
confidence: 99%
“…Propranolol is a non-selective β-adrenoceptor antagonist also frequently used to prevent migraine attacks. However, it has been shown that it has agonist effects on prejunctional 5-HT 1D and 5-HT 1F receptors in trigeminal fibers through which can inhibit the release of CGRP from these fibers that innervate the forehead skin and dura mater [ 117 ]. Interestingly, a single point mutation in the seventh transmembrane domain of the 5-HT 1 receptor increases 100–1000 fold the affinity of β-adrenoreceptor antagonists for the 5-HT 1D/1F receptors [ 127 ].…”
Section: Antimigraine Drugs That Modulate Cgrpmentioning
confidence: 99%
“…Alternatives to antiepileptics include beta-blockers, antidepressants, and OnabotulinumtoxinA. In the case of beta-blockers, propranolol is considered a safe option during pregnancy and breastfeeding; however, it is important to consider that propranolol efficacy has been shown to vary depending on the hormonal status of patients [ 83 ], and when taken in the third trimester, it should be stopped a few days before delivery since there is an increased risk of respiratory depression, neonatal bradycardia, and hypoglycemia [ 73 , 74 , 84 ]. Tricyclic antidepressants like amitriptyline can also be an alternative, but they should be taken with caution since their intake during the third trimester could result in neonatal withdrawal symptoms.…”
Section: Introductionmentioning
confidence: 99%